Horner's syndrome secondary to intervertebral disc herniation at the level of T1–2. (5th June 2014) - Spacey, Kate; Dannawi, Zaher; Khazim, R; Dannawi, Z
Abstract : A 54-year-old Caucasian woman presented with a 6 week history of periscapular pain and a T1 radiculopathy associated with Horner's syndrome. MRI of her cervicothoracic spine revealed an intervertebral disc herniation at the level of T1–2. During investigation she experienced some improvement in her symptoms and a conservative approach was pursued. At 6 months her pain and radiculopathy had resolved, and there was mild residual ptosis.